Interactions between Co-Habitating fungi Elicit Synthesis of Taxol from an Endophytic Fungus in Host Taxus Plants - Soliman, Sameh S.; Raizada, Manish N. (Frontiers in Microbiology, 2013)
Within a plant, there can exist an ecosystem of pathogens and endophytes, the latter described as bacteria and fungal inhabitants that thrive without causing disease to the host. Interactions between microbial inhabitants represent a novel area of study for natural products research. Here we analyzed the interactions between the fungal endophytes of Taxus (yew) trees. Fungal endophytes of Taxus have been proposed to produce the terpenoid secondary metabolite, Taxol, an anti-cancer drug. It is widely reported that plant extracts stimulate endophytic fungal Taxol production, but the underlying mechanism is not understood. Here, Taxus bark extracts stimulated fungal Taxol production 30-fold compared to a 10-fold induction with wood extracts. However, candidate plant-derived defence compounds (i.e. salicylic acid, benzoic acid) were found to act only as modest elicitors of fungal Taxol production from the endophytic fungus Paraconiothyrium SSM001, consistent with previous studies. We hypothesized the Taxus plant extracts may contain elicitors derived from other microbes inhabiting these tissues. We investigated the effects of co-culturing SSM001 with other fungi observed to inhabit Taxus bark, but not wood. Surprisingly, co-culture of SSM001 with a bark fungus (Alternaria) caused a 3-fold increase in Taxol production. When SSM001 was pyramided with both the Alternaria endophyte along with another fungus (Phomopsis) observed to inhabit Taxus, there was an eight-fold increase in fungal Taxol production from SSM001. These results suggest that resident fungi within a host plant interact with one another to stimulate Taxol biosynthesis, either directly or through their metabolites. More generally, our results suggest that endophyte secondary metabolism should be studied in the context of its native ecosystem.